2k+7(-2-6)=

Simple and best practice solution for 2k+7(-2-6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2k+7(-2-6)= equation:


Simplifying
2k + 7(-2 + -6) = 0

Combine like terms: -2 + -6 = -8
2k + 7(-8) = 0

Multiply 7 * -8
2k + -56 = 0

Reorder the terms:
-56 + 2k = 0

Solving
-56 + 2k = 0

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '56' to each side of the equation.
-56 + 56 + 2k = 0 + 56

Combine like terms: -56 + 56 = 0
0 + 2k = 0 + 56
2k = 0 + 56

Combine like terms: 0 + 56 = 56
2k = 56

Divide each side by '2'.
k = 28

Simplifying
k = 28

See similar equations:

| -8(-4+8x)-2x= | | -6=129+23 | | -5k-2(k-7)= | | -4(1+4n)-8= | | -8+2(1-7x)= | | 6x+6(1-x)= | | -3k+8k(3k+3)= | | 11(z+1)-4(z-1)=4(z-3)+2(z-3) | | =7*38 | | 5-x^2=8 | | x^2-14x=5x | | 9-3.6+4= | | 7(7+2)-5= | | 2x^2-3x-5=o | | 17y-y+9=32-19y+82 | | 12y-4y=56 | | 3(x+2)=7(x-1)-7 | | 6x^3-15x^2+12x-3=0 | | 34=-2(22-x)+3(x-4) | | -2x^2+100x-1250=0 | | 14-8x+x^2=0 | | 3x+8x-9x=3+3 | | 22=-2(23-z)+3(z-4) | | 24m^2+m=0 | | 8k-5k(5-3k)= | | -6x+8x(x-1)= | | y=lx-8l | | 4n(n-1)-n= | | 9(z+4)-3(z-2)=2(z-4)+3(z-2) | | -4(5-2r)+1= | | -7x-2(5x-2)= | | n-5(6n-4)= |

Equations solver categories